Costeño struggles for land rights and the control of emergent media spaces in Nicaragua - Cupples, Julie (2018)
This article explores media representations of the current crisis on the Caribbean Coast of Nicaragua and the setbacks to regional struggles for autonomy and land rights posed by this crisis. It provides a detailed analysis of the current conflict in the North Caribbean region, and focuses in particular on how the violent actions of illegal settlers are accelerating insecurity and environmental degradation there, and how organizations such as CEJUDCHAN are using media spaces like YouTube to respond to and intervene in this situation. It also outlines the Rama Kriol people’s struggles against new plans for an interoceanic canal in the South Caribbean. We draw on Boaventura de Sousa Santos’ concept of a “sociology of absences” to analyze both the Nicaraguan government’s inaction, indifference and deceit in the face of indigenous and campesino opposition, and popular practices of oppositional media production and circulation.